180 Falls in children under one year. (1st September 2016) - Mulligan, Christopher S; Brown, Julie; Adams, Susan
Abstract : Background: Falls in children are a common cause of injury and hospital presentation. Compared to older children, infants under age one are likely to have distinctive causation and injury patterns of falls as they are generally not yet fully independently mobile and falls are more directly the responsibility of the caregiver. There is little published on the relevant predictors of injury, mechanistic factors and injury patterns in this age group. Methods: We conducted a retrospective study of children 12 months and under who presented after a fall to a paediatric trauma centre in Sydney, Australia. The circumstances and mechanisms of the fall, injury patterns, burden of investigations and outcomes were analysed. Results: Over a 3 year period (2011–13), a total of 916 children under 1 presented following a fall. 110 were admitted and there was one death. All admitted cases involved a short distance fall. The most common mechanisms were children falling from furniture, baby equipment and being dropped by adults. Patients dropped by others were 3 times more likely to be admitted than children presenting following other fall types. Patients who fell from furniture had significantly longer hospital stays. Head injury was the most common reason for admission (85%). Twenty patients had severe injuries (Abbreviated Injury Score >15). There were 7 neurosurgical and 12 orthopaedic/general surgical operations performed. There was no association between injury mechanism and severity. Twenty patients were referred to the Child Protection Unit for investigation and the rate of non-accidental injury in admitted patients was 5%. Conclusions: Fall mechanisms involving children being dropped by adults, and falls from cots, beds or couches carry the highest clinical burden. These mechanisms should be targets for injury prevention and inform the design of safe equipment and environments for babies.